The Predictive Ability Of Academic Psychological Capital And Academic Confidence In Academic Adjustment During Online Learning Among University Students - Elkasaby, Wesam Hamdy; Shalaby, Youssef Mohmed (Migration Letters, 2024)
The aim of the research is to predict the academic adjustment of university students through academic psychological capital and academic confidence, to identify the level of academic psychological capital of university students and to detect differences in study variables according to gender and university stage of study. The research sample consisted of (209) students (96 male students, 113female students) randomly selected from the students of the Faculty of Education at King Khalid University, at the undergraduate and graduate levels with an mean age of (34.6) and a standard deviation of (8.45), applied to them: academic capital scale, academic adjustment scale, and academic confidence scale. The results of the research concluded that academic psychological capital and academic confidence predict of academic adjustment among university students. The results also showed a high level of academic psychological capital among the sample members, and the absence of significant differences in the three research variables (academic psychological capital – academic adjustment – academic confidence) attributed to the gender variable.